2013
DOI: 10.1111/ajco.12066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic value of four tumor markers in bronchoalveolar lavage fluid of peripheral lung cancer

Abstract: The assay of these tumor markers in BALF may be used as a diagnostic tool to complement a cytological examination in the diagnosis of peripheral lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…However, the clinical practical value of serum SCC-Ag is still controversial. The numerical changes of SCC-Ag do not specifically reflect cervical cancer; increased SCC-Ag levels have also been observed in patients with lung cancer, esophageal SCC and other benign diseases (3638). More unfortunately, the autofit cut-off level of SCC-Ag is still a matter of debate partially due to the different disease stages of patient groups (39).…”
Section: Discussionmentioning
confidence: 97%
“…However, the clinical practical value of serum SCC-Ag is still controversial. The numerical changes of SCC-Ag do not specifically reflect cervical cancer; increased SCC-Ag levels have also been observed in patients with lung cancer, esophageal SCC and other benign diseases (3638). More unfortunately, the autofit cut-off level of SCC-Ag is still a matter of debate partially due to the different disease stages of patient groups (39).…”
Section: Discussionmentioning
confidence: 97%
“…However, single marker of lung cancer shows low diagnostic specificity and sensitivity, having poor value for the diagnosis of lung cancer (Leidinger et al, 2010). Therefore, there is a consensus that a combination of markers can increase the diagnostic specificity and sensitivity than single marker (Schneider et al, 2002;Farlow et al, 2010;Wang et al, 2013;Li et al, 2014). For example, in diagnosing some malignant tumors, such as prostate or ovarian cancer, by combining multiple biomarkers data, the diagnostic performance was improved rapidly than individual serum biomarker (Amsellem-Ouazana et al, 2005;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Li et al . identified that BALF was superior to serum specimens for detection of CEA, NSE, CYFRA21‐1 and SCC‐Ag. However, the value of some new markers such as USP8 for the diagnosis of peripheral pulmonary carcinoma in BALF was not clear.…”
Section: Resultsmentioning
confidence: 99%